Teach Aquaculture Curriculum: Spawning and Rearing Bivalve Molluscs--Larval Culture - R. Leroy Creswell; Cortney L. Ohs; Craig S. Kasper; Carlos V. Martinez; Elisa J. Livengood; Amber L. Garr; Frank A. Chapman; Brian E. Myers (EDIS)
FA175, a 4-page activity by R. Leroy Creswell, Cortney L. Ohs, Craig S. Kasper, Carlos V. Martinez, Elisa J. Livengood, Amber L. Garr, Frank A. Chapman, and Brian E. Myers, is activity 13 of the Teach Aquaculture Curriculum. In this activity for grades 9-12, students learn to describe the reproductive biology and spawning of bivalve molluscs, leading to an understanding of the conditions used in hatcheries for commercial production of bivalve molluscs. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, July 2010.